Routledge handbook of democratization - Haynes, Jeffrey (Routledge, 2018)
This handbook provides a global overview of the process of democratization, with chapter-by-chapter discussion at the country and regional levels, examining the interaction between the domestic and external factors that affect the progression of countries from authoritarian to democratic rule.